Article Effect of Carbon Content and Intercritical Annealing on Microstructure and Mechanical Tensile Properties in Fecmnsicr Trip-Assisted Steels - Monsalve-Gonzalez, A; Artigas-Abuin, A; Tesser-Diaz, E; Silva-Molina, C; Silva-Molina, C (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Four TRIP (Transformation Induced Plasticity) assisted steels, three TBF (TRIP Bainitic Ferrite) steels and one TPF (TRIP Polygonal Ferrite) steel, were manufactured from three different carbon contents (0.2, 0.3 and 0.4 wt.% C), to study the evolution of their microstructure and tensile mechanical properties in 15 mm thick plates. TBF steels were subjected to the same austenitization heat treatment and subsequent bainitization isothermal treatment. The TPF steel was subjected to an intercritical annealing and subsequent isothermal bainitization treatment. All were microstructurally characterized by optical, scanning electron and atomic force microscopy, as well as X-ray diffraction. Mechanically, they were characterized by the ASTM E8 tensile test and fractographies. For the TBF steels, the results showed that when the carbon content increased, there were an increase in volume fraction of retained austenite, of the microconstituent “martensite/retained austenite” and in the tensile strength; and a decrease in the volume fraction of bainitic ferrite matrix and elongation; with an improvement in TRIP behavior due to the increase in retained austenite. The TPF steel presented around 50% ductile polygonal ferrite developing better TRIP behavior than the TBF steels. The evolution of the fractographies was ductile to brittle for TBF steels with an increase in carbon content, and for TPF, the appearance of the fracture surface was ductile. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.